MODELING AND ANALYSIS OF AC-AC SOFT STARTER FOR INDUCTION MOTOR BASED ON THYRISTOR AND IGBT - Anisa Harumwidiah; Adi Kurniawan (ASEAN Journal of Systems Engineering, 2015)
Motor Starting on large capacity induction motor using direct on-line starting (DOL) method may cause a problem for system. It is due to motor start-up current that can be up to eight times of the nominal current. Soft starter is an induction motor starting method based on power electronic that can significantly decrease motor starting current, resulting in reduced fuel consumption. In this research, a comparison between DOL starting method and two soft starter methods based on thyristor and Insulated Gate Bipolar Transistor (IGBT) is performed. The results show that thyristor based soft starter method with firing angle 90˚ can reduce input voltage from 220 V to 165 V so that the maximum starting current down from 633 A to 265 A. In the same voltage value, IGBT can reduce maximum starting current to only 100 A